The Potential of Religious Tourism and Strategies for Its Development in Supporting the Tourism Industry of North Sumatra in the Digital Age - Muhammad Naufal Faqihul Aalam; Slamet Widodo; Elfitra Desy Surya (AMK : Abdi Masyarakat UIKA, 2026)
Religious tourism is an aspect of tourism with significant potential to support regional economic growth, cultural preservation, and the strengthening of the community’s spiritual values. North Sumatra Province boasts a diversity of religions, cultures, and religious sites that serve as tourist attractions, such as the Al-Mashun Grand Mosque in Medan, the Graha Maria Annai Velangkanni Shrine, the Gunung Timur Buddhist Temple, and various religious destinations in the Lake Toba area and its surroundings. In the digital era, the development of religious tourism relies not only on the construction of physical infrastructure but also on the utilization of digital technology in promotion, marketing, and tourism services. This article aims to analyze the potential of religious tourism in North Sumatra and its development strategies to support the tourism industry in the digital era. The research method used is a descriptive qualitative approach involving literature review and secondary data analysis. The results indicate that religious tourism in North Sumatra holds significant potential for development through the integration of digital technology, strengthened collaboration between the government and the community, improved infrastructure quality, and the development of social media-based promotions and digital platforms.